Effect of inhaled frusemide and oral indomethacin on the airway response to hypertonic saline challenge in asthmatic subjects. Issue 1 (January 1997) - Rodwell, L T; Anderson, S D; Spring, J; Mohamed, S; Seale, J P
Abstract : BACKGROUND: Inhaled frusemide inhibits airway narrowing and causes a transient increase in forced expiratory volume in one second (FEV1) during hypertonic saline challenge. This inhibitory effect could be secondary to prostaglandin release during challenge. The involvement of prostaglandins in the inhibitory action of frusemide during challenge with 4.5% NaCl was investigated by premedicating with indomethacin, a prostaglandin synthetase inhibitor. METHODS: Fourteen asthmatic subjects (eight women) aged 26.6 (range 18-56) years participated in a double blind, placebo controlled, crossover study. The subjects attended five times and inhaled 4.5% NaCl for 0.5, 0.75, 1, 1.5, 2, 4, 8, 8, and 8 minutes, or part thereof, or until a provocative dose causing a 20% fall in FEV1 (PD20 FEV1) was recorded. Indomethacin (100 mg/day) or placebo were taken three days before all visits, except control day. The FEV1 was measured and frusemide (38.0 (6.4) mg, pH = 9) or vehicle (0.9% NaCl, pH = 9) were inhaled 10 minutes before the challenge. Bronchodilation was calculated as the percentage rise in FEV1 from the prechallenge FEV1 to the highest FEV1 recorded during the challenge. RESULTS: Frusemide caused a fold increase in PD20 FEV1 compared with the vehicle which was similar in the presence of both indomethacin and placebo (3.7 (95% CI 2.0 to 7.3) versus 3.3 (2.0 to 5.4)). Frusemide, but not vehicle, also caused a transient percentage rise in FEV1 during challenge with 4.5% NaCl which was not blocked by indomethacin (3.6% (1.2 to 6.0)) or placebo (3.1% (1.0 to 5.2)). CONCLUSIONS: Inhaled frusemide inhibited airway narrowing and caused a transient increase in FEV1 during challenge with 4.5% NaCl. These effects were not blocked by indomethacin, which suggests that the inhibitory action of frusemide is not secondary to prostaglandin release.